Are central bank preferences asymmetric? A comment - Patrick Minford; Naveen Srinivasan (Cardiff University, Cardiff Business School, 2008)
A recent paper by Ruge-Murcia [European Economic Review 48 (2004), 91-107] on asymmetric central bank objectives provides a new perspective on the policy roots of inflation in developed economies. More precisely, the paper demonstrates that if the distribution of the supply shocks is normal, then the reduced form solution for inflation implies a positive (or negative) relation between average inflation and the variance of shocks. We argue that the evidence offered in support of this hypothesis suffers from lack of identification because Phillips curve nonlinearity combined with quadratic central bank preferences yield the same reduced form solution for inflation. If so, estimating reduced form for inflation will not be able to discriminate between these models. Yet they have quite different implications for policy. Other, structural, evidence is needed.
Keywords: E52; E58; E61; 330; Preference asymmetry; Phillips curve nonlinearity; Identification; Zentralbank; Geldpolitik; Inflation; Phillips-Kurve; Theorie